THE IMPLEMENTATION OF BUILDING WORDS IN IMPROVING VOCABULARY MASTERY OF THE SECOND GRADE STUDENTS OF SMPN 1 MAJAULENG - Mellyana Mellyana; Rizka Indahyanti; Muthmainnah Mursidin (English Education Department, Faculty of Teacher Training and Education, Universitas Islam Makassar, 2024)
This study evaluates the effectiveness of the Building Words method in enhancing vocabulary mastery among second-grade students at SMPN 1 Majauleng. Employing a pre-experimental one-group pretest-posttest design, the research involved 30 randomly selected students. Data were collected through pretest and posttest, with an intervention using the Building Words method between the two tests. Results show a significant improvement in students' average vocabulary scores, from 31 in the pretest to 91 in the posttest. Statistical analysis using paired t-test yielded a t-value of -81.168 with a p-value of 0.000, confirming the method's effectiveness. Students' ability classification shifted dramatically from